Digitalisasi melalui Aplikasi Canva dalam Meningkatkan Kualitas Packaging Produk Usaha Mikro Kecil dan Menengah (UMKM) di Desa Lubuk Leban OKU - M. Agus Kurniawan; Nourma Wulanda; Darman Syafei (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This community service activity aims to enhance the competitiveness and marketing capacity of Micro, Small, and Medium Enterprises (MSMEs) in Lubuk Leban Village, Ogan Komering Ulu Regency, through the utilization of digital design technology using Canva for product packaging. Most local MSMEs previously relied on traditional and unbranded packaging, limiting their market penetration and brand perception. The method applied in this initiative consisted of participatory appraisal, interactive workshops, hands-on packaging design assistance, and product labeling evaluation. The result showed a significant transformation in participants' digital literacy and packaging aesthetic standards. Over 85% of participating MSME owners successfully created modern, branded, and informative packaging labels independently using Canva. Furthermore, the upgraded packaging enhanced product appeal, shelf life perception, and market readiness for broader retail distribution. This program demonstrates that accessible digital tools like Canva play a pivotal role in accelerating rural economic empowerment. By improving packaging quality, local products have greater opportunities to compete in the digital market and modern retail market, so that this activity contributes to strengthening the economic independence of rural communities in a sustainable manner.